Improving the System of Issuing Surrogacy Permits and its Legal Framework (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
For humanity, the issue of family and especially childbirth is considered sacred at any time and in any space. There is also a specific history of surrogacy, one of the methods considered as a solution to the problem of infertility in the current developed period. The author develops his own author's definition in this regard, with a comparative analysis of the experience of the United States and France in this matter, as well as various definitions of surrogacy.